PERLINDUNGAN HUKUM BAGI KONSUMEN PENGGUNA JASA PARKIR DI KLINIK PRATAMA TANJUNG BERDASARKAN PERATURAN DAERAH KABUPATEN BANYUMAS NOMOR 4 TAHUN 2021 - Zul Fauzi, Nizar; Wati, Endang Eko; Sukirno (Faculty of Social, Economics and Humanities, 2024)
This research aims to find out the legal protection for consumers who used parking services at the Tanjung Pratama Clinic, Banyumas Regency based on Banyumas Regency Regional Regulation Number 4 of 2021 concerning the Implementation of Parking associated with consumer protection law, and find out the obstacles faced in efforts to provide legal protection for consumers. This research used descriptive method to obtain descriptive data regarding the provision of legal protection to consumers of parking service users and the obstacles faced in efforts to provide legal protection. Normative juridical research was used to analyse legal protection for consumers of parking services at Tanjung Primary Clinic. While empirical juridical research was used to analyse the obstacles faced in efforts to provide legal protection for consumers of parking service users at the clinic. Data obtained using primary data and secondary data. Based on the results of the research, it is concluded that the Regional Regulation of Banyumas Regency Number 4 of 2021 concerning the Implementation of Parking serves as a guideline in the implementation of parking. Normatively, the regulation of consumer rights also refers to Article 4 of Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection. Consumer rights that must be protected in the research based on Banyumas Regency Regional Regulation Number 4 of 2021 concerning the Implementation of Parking associated with Consumer Protection Law are the right to security, comfort and safety, the right to have their opinions and complaints heard, the right to compensation, compensation, and/or replacement, if the services received are not in accordance with the agreement or not as they should be. The obstacles faced in efforts to provide legal protection for consumers who use parking services at the Tanjung Pratama Clinic, Banyumas Regency are institutional constraints, funding, human resources, regulations and information.